Kesan aplikasi perisian cerita interaktif semasa mengajarkan kemahiran bacaan dan kefahaman dalam kalangan murid tahun 4 di Brunei Darussalam - Yahya Othman,; Dayang Rini Pakar, (Penerbit UKM, 2011)
The purpose of this study was to assess students’ achievement in reading and comprehension when using traditional method and application of interactive computer aplication. In addition, this study also evaluates the impact of using CD-ROM interactive stories in the teaching of reading including the aspect of knowledge, morphology and syntax among the average students. A quasi-experimental method was used in this study. The study sample involved 52 students of year 4 from one primary school in Brunei Muara District. The sample was divided into two groups, the experimental group and the control group. Each group consisted of 26 average students comprising 13 boys and 13 girls. The results of this study were analyzed using t-test independent samples to assess whether there are significant differences in the mean performance of reading comprehension, mastery of morphology and syntax between the experimental and control groups in pre and post test. T-test analysis showed that there was a significant difference in the mean of reading comprehension performance between the experimental group and the control group in the post-test. The findings also show that the use of CD-ROM interactive stories in teaching reading and comprehension not only enhance students' performance in comprehension, but also enhance other aspects of language such as the morphology and syntax